2018
DOI: 10.1002/dta.2478
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietic effects of low‐dose cobalt application

Abstract: Cobaltous ions (Co ) stabilize HIFα, increase endogenous erythropoietin (EPO) production, and may, therefore, be used as a performance-enhancing substance. To date, the dosage necessary to stimulate erythropoiesis is unknown. The aim of this study was, therefore, to determine the minimum dosage necessary to increase erythropoietic processes. In a first double-blind placebo-controlled study (n = 5), single oral Co dosages of 5 mg (n = 6) and 10 mg (n = 7) were administered to healthy young men. Cubital venous b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 32 publications
1
15
1
1
Order By: Relevance
“…For the current protocol, the urine Co 2+ concentrations reported during the 3-week treatment period are in accordance with data from the literature (Krug et al, 2014 ) and our own experience (Hoffmeister et al, 2018 ). Because most of the ingested cobalt is not absorbed, and because excretion via feces is the main route for elimination of ingested Co 2+ , urinary excretion accounts for between 10 and 27% of ingested Co 2+ (Ayala-Fierro et al, 1999 ; Hoffmeister et al, 2018 ). The relatively high inter-individual variation of urine Co 2+ observed in this study may therefore be attributable to differences in gastrointestinal Co 2+ absorption, while the intra-individual variation in the morning urine samples may also be due to different diuresis.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…For the current protocol, the urine Co 2+ concentrations reported during the 3-week treatment period are in accordance with data from the literature (Krug et al, 2014 ) and our own experience (Hoffmeister et al, 2018 ). Because most of the ingested cobalt is not absorbed, and because excretion via feces is the main route for elimination of ingested Co 2+ , urinary excretion accounts for between 10 and 27% of ingested Co 2+ (Ayala-Fierro et al, 1999 ; Hoffmeister et al, 2018 ). The relatively high inter-individual variation of urine Co 2+ observed in this study may therefore be attributable to differences in gastrointestinal Co 2+ absorption, while the intra-individual variation in the morning urine samples may also be due to different diuresis.…”
Section: Discussionsupporting
confidence: 90%
“…In our recent study (Hoffmeister et al, 2018 ), we demonstrated that a 5-day Co 2+ administration of 10 mg/day clearly passes the erythropoietic threshold, as indicated by increased plasma [EPO], a higher percentage of IRF, and decreased plasma ferritin concentration. Smaller dosages as 0.45 mg/day for 2 weeks (Tvermoes et al, 2013 ) and 1 mg/day for 90 days did not show any effect (Tvermoes et al, 2014 ) but a Co 2+ application of 5 mg/day for 5 days showed a tendency toward erythropoietic stimulation (Hoffmeister et al, 2018 ).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Cobalt participates in many adaptive processes, affects the cardiovascular system and vasodilation [11]. There is evidence of cobalt influence on erythropoiesis [12]. However, in our study, no correlation was found between hair cobalt content and hemoglobin level.…”
Section: Resultscontrasting
confidence: 68%
“…An important aspect of the problem under discussion is that cobalt mineral salts, those which are not part of cobalamins, can have their own regulatory effect on the state of metabolic processes in a human body. Cobalt salts (Co2+) have been used for a long time as a pharmacological stimulators of hematopoiesis in the treatment of anemias [41,42]. Further studies have shown that hypoxiainducible factor is the leading mediator that determines the pathway and intensity of the effects of cobalt mineral salts on a human body.…”
mentioning
confidence: 99%